An artificial chromosome for data storage. Issue 5 (12th February 2021) - Chen, Weigang; Han, Mingzhe; Zhou, Jianting; Ge, Qi; Wang, Panpan; Zhang, Xinchen; Zhu, Siyu; Song, Lifu; Yuan, Yingjin
Abstract: DNA digital storage provides an alternative for information storage with high density and long-term stability. Here, we report the de novo design and synthesis of an artificial chromosome that encodes two pictures and a video clip. The encoding paradigm utilizing the superposition of sparsified error correction codewords and pseudo-random sequences tolerates base insertions/deletions and is well suited to error-prone nanopore sequencing for data retrieval. The entire 254 kb sequence was 95.27% occupied by encoded data. The Transformation-Associated Recombination method was used in the construction of this chromosome from DNA fragments and necessary autonomous replication sequences. The stability was demonstrated by transmitting the data-carrying chromosome to the 100th generation. This study demonstrates a data storage method using encoded artificial chromosomes via in vivo assembly for write-once and stable replication for multiple retrievals, similar to a compact disc, with potential in economically massive data distribution. Abstract : A 254 kb artificial chromosome, storing two pictures and one video clip encoded with low-density parity-check codes and pseudo-random sequences, was manufactured and transmitted from generation to generation stably. The digital information residing in the chromosome was fast retrieved, tolerating base insertions and deletions in nanopore readout.